INTERPERSONAL COMMUNICATION STRATEGY FOR MAINTAINING POST-VIOLENCE RELATIONSHIP - AULIA NURHASANAH, LISTIA; Naryoso, S.Sos, M.Si, Agus (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2017)
Annual Notes (CATAHU) 2016 The National Commission on Violence Against Women (Komnas Perempuan) shows that dating violence continues to increase from year to year. The fact that dating violence does not yet have a strong legal protection like domestic violence is what keeps many cases of violence going on and destroying courtship relationships. But in fact, many couples who have experienced violence but still able to maintain their relationship until now. Research that aims to know about interpersonal communication strategy to maintain the relationship of courtship after violence uses a qualitative descriptive approach with interpretive paradigm to help interpret and understand attitudes. This study uses a phenomenological approach, with Dating Violence Theory, Interpersonal Communication Theory, Conflict Attribution Theory, Relational Maintenance Theory, and Emotion and Communication Theory. The study will be conducted on six people (3 pairs) of informants, which is composed of dating partner with 1 year long relationship, couple with 2 years long relationship, and couple with 6 years relationship. The results of this study all couples have experienced violence both psychic, physical and sexual, but in psychic violence not all dating partners are aware when doing or becoming victims of violence. Both women and men in this study had been perpetrators or victims of psychic and physical violence in courtship. However, this study revealed that only the women who ever felt to get the act of sexual violence from their partners, that is when felt forced to respond to sexual desire from their partners. They claim to continue doing it because they feel obliged to satisfy the sexual desires of their partners. Communication strategies conducted by courtship who have experienced violence through verbal and novetic communication activities are very important and necessary in maintaining courtship relationships woven. In addition to helping cure the pain of violence, spending time together to hangout and telling strories can be a nurturing in the affection and quality of post-violence relationships. Keeping the rules together, keeping commitments, resolving conflicts with openness, seeking win-win solutions, controlling emotions, mutually memorizing, always be there for each other, giving surprises to please couples, Hearing complaints and giving support to each other can also be an effort that couples make to maintain relationships.